2022
DOI: 10.1177/22799036221115780
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 stigmatization: A systematic literature review

Abstract: Covid-19 has severe implications for the emergence of negative stigmatization of specific individuals and community groups. Due to labeling and discrimination, mental attacks cause psychological distress so seriously that it requires proper handling. Therefore, this study aims to conduct a systematic literature review on articles on COVID-19 stigmatization. This paper used descriptive analysis that 248 articles are from the Scopus database obtained by keyword Covid-19 stigmatization in the 2020–2021 time span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…However, some people experienced these concerns at a more extreme level and show “health anxiety” symptoms (Heinen et al, 2022). Consistent with a former study’s finding (O’Bryan & McLeish, 2017) showing that individuals who have difficulty in tolerating uncertainty and who need cognitive clarity are more likely to experience health anxiety, our findings support the idea that these people are also inclined to stigmatize individuals and health care professionals infected with COVID-19 through their anxiety (Kartono et al, 2022; Smith et al, 2022). Having the need for cognitive clarity during the outbreak may predispose individuals to overly worry and exaggerate that irrelevant symptoms in their bodies are the symptoms of COVID-19.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, some people experienced these concerns at a more extreme level and show “health anxiety” symptoms (Heinen et al, 2022). Consistent with a former study’s finding (O’Bryan & McLeish, 2017) showing that individuals who have difficulty in tolerating uncertainty and who need cognitive clarity are more likely to experience health anxiety, our findings support the idea that these people are also inclined to stigmatize individuals and health care professionals infected with COVID-19 through their anxiety (Kartono et al, 2022; Smith et al, 2022). Having the need for cognitive clarity during the outbreak may predispose individuals to overly worry and exaggerate that irrelevant symptoms in their bodies are the symptoms of COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Health anxiety arises from interpreting bodily sensations as an indicator of a serious illness and includes one’s over concern about his/her health as a result of this misinterpretation (Salkovskis et al, 2002). Anxiety, fear, and worry have been among the stable predictors of stigmatizing attitudes toward patients and health care workers during the pandemic (Kartono et al, 2022; Smith et al, 2022). It was shown that stereotypical beliefs about certain groups were likely to elicit fear which hence triggered stigmatizing attitudes and behaviors toward these groups (Thonon & Larøi, 2017).…”
mentioning
confidence: 99%
“…The first is the stigmatisation of the disease because there will be many unknown things about the disease. Poor knowledge and understanding of a disease condition can lead to stigmatisation just as seen in HIV37 38 and COVID-19 39 40. Stigmatisation has contributed to avoidable mortalities from cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of discrimination experienced from the time of the early waves to the later waves of COVID-19 may be accounted for by the accumulation of public knowledge relating to COVID-19 over time. The more knowledge the public gains about COVID-19, the weaker the stigmatic climate should be 15 and the amount of knowledge about COVID-19 held by the public increases as time passes 17 . The risks of being blamed for one's own COVID-19 infection to experiencing psychological distress were indicated to be higher in those who were infected in the later waves than those infected in the earlier wave, although the experiences of some forms of discrimination and participants being maligned for having been infected with COVID-19 were not signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination is suggested to be less frequently experienced by those who were infected in the later waves than those infected in the early waves, while previous studies accounting for the difference have not provided su cient explanation for this nding. The amount of public knowledge about COVID-19 associates with the degree of stigma including discrimination toward COVID-19 15,16 . Knowledge relating to COVID-19 increases gradually among the general population as time passes 17 .…”
Section: Introductionmentioning
confidence: 99%